The Field of Play: An Ecology of Being in Music Therapy - Carolyn Kenny (Voices, 2014)
This text tells the story of the development of the theory, The Field of Play, through the developmental lens of Carolyn Kenny, who crafted the theory.  It emphasizes the integration between individual, culture, profession, and the natural world.  It is crafted in a performative writing style that emphasizes the oral tradition so prevalent in the Indigenous worldview and experience.